The Influence of Company Size, Profitability and Business Risk on Capital Structure in Indonesia - Windiartik; Dewi, Nurma Gupita (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to examine company size, profitability, and business risk on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange during 2020-2022. This type of research is quantitative research. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange during 2020-2022. The sample in this research was obtained using a purposive sampling method. The data analysis technique used in this research is the multiple regression analysis method using the Statistical Product and Service Solution (SPSS) program. The results of this study indicate that company size has a positive and insignificant effect on capital structure. Profitability has an insignificant negative effect on capital structure and business risk has an insignificant negative effect on capital structure